2003
DOI: 10.1046/j.1471-5740.2003.00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cleaning methodologies used for removal of physical, chemical and microbiological residues from produce

Abstract: An increasing number of disease outbreaks have been associated with produce, while pesticide levels continue to be a safety concern. With increased health awareness, fresh produce consumption has increased. As there is a need for microbial and pesticide removal intervention measures of proven efficacy to maintain confidence in food service produce preparation, a series of experiments were undertaken. Produce cleaning methods were tested by measuring removal of gross dirt, wax and environmental contaminants pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Ultrasound is also considered a clean technology, as are other recently suggested sanitizer alternatives, such as electrolyzed water (Rahman, Ding, & Oh, 2010). Considering that the US Environmental Protection Agency (EPA) Scientific Advisory panel has stated that any treatment which can reduce microbial contamination by 2 logs would be significant and that any new sanitizer or test method presented should be compared to 200 mg/L chlorine as a standard for efficacy (Michaels, Gangar, Schattenberg, Blevins, & Ayers, 2003), we can conclude that the combination of peracetic acid and ultrasound has great potential to replace chlorine in the sanitization step of fresh fruits and vegetables. However, peracetic acid should always be handled in a dry and ventilated and avoided the incidence of direct sunlight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound is also considered a clean technology, as are other recently suggested sanitizer alternatives, such as electrolyzed water (Rahman, Ding, & Oh, 2010). Considering that the US Environmental Protection Agency (EPA) Scientific Advisory panel has stated that any treatment which can reduce microbial contamination by 2 logs would be significant and that any new sanitizer or test method presented should be compared to 200 mg/L chlorine as a standard for efficacy (Michaels, Gangar, Schattenberg, Blevins, & Ayers, 2003), we can conclude that the combination of peracetic acid and ultrasound has great potential to replace chlorine in the sanitization step of fresh fruits and vegetables. However, peracetic acid should always be handled in a dry and ventilated and avoided the incidence of direct sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound was adopted by the electronics industry to decontaminate surfaces and its use has recently been recommended as an alternative sanitization step in the food industry (Adekunte, Tiwari, Scannell, Cullen, & O 0 Donnell, 2010;Cao et al, 2010;Knorr, Zenker, Heinz, & Lee, 2004;Lee, Heinz, & Knorr, 2003;Nascimento et al, 2008;Sagong et al, 2011). When applied to liquids, ultrasonic waves promote the occurrence of the cavitation phenomenon, which consists of the formation, growth and collapse of air bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…The packing process before shipment to retail outlets was generally effective in removing pesticides that may be present on peel at the time of harvest. Tests on waxed and unwaxed apples contaminated with a cocktail of pesticides showed that treatments including wiping with paper towels were more effective than other procedures for pesticide removal (Michaels et al 2003). b) Storage: Lemons, oranges and grapefruits were dipped in a solution of diphenyl, o-phenyl phenol, 2,4-dichlorophenoxyacetic acid (2,4-D), imazalil, thiabendazole, benomyl and sec-butylamine or fumigated with methyl bromide and stored at 14°C.…”
Section: Postharvest Handlingmentioning
confidence: 99%
“…Various methods were tested for removing pathogens, pesticides and other contaminants from the surfaces of fresh fruits and vegetables (Michaels et al 2003 ). A range of fresh produce was subjected to different combinations of cleaning processes, such as water rinsing steps, use of produce-cleaning brushes, disinfectants, air drying and paper towels.…”
Section: Washingmentioning
confidence: 99%